Grafiki Anonima z lat 1980-1985 [arkusz znaczków podziemnych] . Posters by an Anonymous Author 1980-1985. Sheet of unofficial stamps - Poczta Solidarność - Fundusz Oporu. (Poczta Solidarność - Fundusz Oporu, 1985)
Black and red print on white paper without perforation. Sheet with "Poczta Solidarność" and "Fundusz Oporu" imprints represents five posters by an anonymous artist from the years 1980-1985, related to Solidarity. Price: 50 zł per stamp.